PRACTISE - PhaRmAcist-led CogniTIve Services in Europe: survey protocol and pilot study - Isenegger, Tamara L. (2017)
Poster presented at the 45th European Symposium on Clinical Pharmacy: Clinical pharmacy tackling inequalities and access to health care. [ESCP (European Society of Clinical Pharmacy)]. 4–6 October 2016, Oslo Norway